Implementation of Effective Smoking Cessation Strategies for People Living with HIV in one Infectious Diseases Clinic, A Pilot Implementation Study - Sigler, Rachel; Robertson, Kelly; Herrman, Megan; Newman, Jessica (Kansas Journal of Medicine, 2022)
Introduction. Use of tobacco products carries significant long-term health risks, and rates of smoking in persons living with HIV are as high as 2-3 times that of the general population. We aimed to increase assessment of readiness to quit smoking and provide cessation counseling to patients receiving HIV care through our clinic.Methods. This study was a pilot implementation in a single-center teaching hospital. In total, 603 active patients with HIV were followed in clinic at the time of the study start; of these, 79 were active tobacco smokers (13%) and eligible for the intervention. Providers were educated on recommendations for tobacco smoking cessation counseling, intervention strategies and options for treatment. Patients who smoked tobacco were assessed for readiness to quit. Cessation counseling and tobacco cessation mediations/nicotine replacement were provided at the discretion of the patient and physician based on visit discussions. Primary outcome measures were increase in assessment of readiness to quit and in providing cessation counseling. Secondary measures included tabulation of number of patients provided with a tobacco smoking cessation treatment and in those with a successful quit episode.Results. There was a moderate increase in patients assessed for readiness to quit and who received tobacco smoking cessation counseling and treatment medications during the pilot. In total, 11 patients (8.7%) reported quitting smoking for at least 2 weeks.Conclusions. Additional work on streamlined mechanisms to identify tobacco use and provide efficient and effective tobacco smoking cessation counseling are needed in this high-risk population.